2011
DOI: 10.1007/978-90-481-2543-2
|View full text |Cite
|
Sign up to set email alerts
|

Innovations as Key to the Green Revolution in Africa

Abstract: This chapter presents the results of studies on a production system calJed Dryland Eco-Farm (DEF) that addresses a range of constraints to agricultural productivity in dryland Africa. It combines the use of live hedges and alJeys of Acacia colei, "demi-Iunes" in which are planted domesticated Ziziphus mauritiania. Annual crops like pearl millet (Pellllisetumglaucu111 (L.) R.Br.), cowpeas and roselle (Hibiscus sabdariffa) are planted in rotation. This trial teststhe effect of the system on (1) soil erosion cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Acacia albida Del. ), commonly referred to as Apple-ring acacia (Barnes and Fagg 2003), is a multipurpose leguminous tree species belonging to the mimosoideae subfamily (Dangasuk et al 2011). It is widespread and commonly found in all tropical Africa from Senegal to Sudan and as far as Natal or Angola (Danthu et al 2002).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Acacia albida Del. ), commonly referred to as Apple-ring acacia (Barnes and Fagg 2003), is a multipurpose leguminous tree species belonging to the mimosoideae subfamily (Dangasuk et al 2011). It is widespread and commonly found in all tropical Africa from Senegal to Sudan and as far as Natal or Angola (Danthu et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…It is also known to grow on the banks of seasonal and perennial rivers and streams on sandy alluvial soils or on flat land where Vertisols predominate. It is very important for agro-silvopastoral as well as soil conservation and soil fertility improvement throughout the arid and semi-arid areas (Dangasuk et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Documented reports (Rajesh et al, 2003;Veeken et al, 2005, Janvier et al, 2007, Lazcano et al, 2009Yadessa et al, 2010) have indicated that amending agricultural soils with organic matter aided plant nutrition and enhanced physicochemical and biological characteristics of the soil on the field. The use of mineral and organic sources of nutrient in varied proportion evolved from long experiences in soil fertility management (Rajesh et al, 2003;Bationo & Waswa, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…26 genera and 520 species (Schrire 1988, Chen & Huang 1993, Bailey et al 1997. Species of Fabaceae have an immense ecological, agricultural and economic importance as nitrogen fi xers (Soltis et al 1995, Crews 1999, Mafongoya et al 2004, Wojciechowski et al 2004, Tobita et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…(Linné 1753:746;Candolle 1825:353), are known to occur in the Americas (Huang & Ohashi 2010), where they are not native. The introduction of plants of these species is usually intentional, due to their use as forage crops (Gramshaw et al 1987, John & Thengane 1994, Tobita et al 2011, and secondarily also because of their medicinal properties, especially for treating wounds and fractures (Huang & Ohashi 2010). However, these Alysicarpus species have also raised conservation concerns, as they can be considered potentially invasive species (Cowie & Werner 1993, Sánchez-Blanco et al 2012.…”
Section: Introductionmentioning
confidence: 99%